LEGITIMACY, AUTHORITY AND MOBILITY IN A MULTI-SCALAR UNIVERSITY CLASS MEDIATED BY WEB TECHNOLOGIES - Gargioni, Ana Alice dos Passos; de Moura, Carolina Bottosso; Lima, Regiane da Silva Macedo; de Anunciação, Renata Franck Mendonça; Grando, Roziane Keila; Araújo, Izabel Cristina de (Revista da Anpoll, 2016)
The aim of this article is to identify and describe the interactional flow dynamics between participants of a course developed using web technology mediation by a consortium of graduate programs in different Brazilian states in the first half of 2015. Based on the analysis of multimedia records on the development of the course, three interaction spaces, or locales, are identified and described between the participants of the course (Skype, live-and-in-person learning classes and Wikispaces), understood as heterogeneous spaces, but interwoven through technological mediation. Based on the affordances and constraints of the technologies used, as well as multi-scale topography observed in these spaces, the interactional flow at and through each level is not linear, as it is governed by legitimacy and authority parameters that not only refer to the conventional school participation modes, but also point to more complex ones. This work is licensed under a Creative Commons Attribution 3.0 License.